PHYTOPLANKTON DIVERSITY IN THE WATERS OF LAKE SIBILI PALU CITY CENTRAL SULAWESI - Miswan Miswan; Sicilia Intan Safitri Ranga; Muhammad Fajri Ramadhan Muslim Shaleh; Umrah Umrah (Biology Department, Mathematics and natural science, Tadulako University, 2022)
The study